Identification of a novel xanthan-binding module of a multi-modular Cohnella sp. xanthanase - Han, Rui; Baudrexl, Melanie; Ludwig, Christina; Berezina, Oksana V.; Rykov, Sergey V.; Liebl, Wolfgang (Frontiers in Microbiology, 2024)
A new strain of xanthan-degrading bacteria identified as Cohnella sp. has been isolated from a xanthan thickener for food production. The strain was able to utilize xanthan as the only carbon source and to reduce the viscosity of xanthan-containing medium during cultivation.Cohnella sp. after growth on different media led to the identification of a xanthanase designated as CspXan9, which was isolated after recombinant production in Escherichia coli. CspXan9 could efficiently degrade the -1,4glucan backbone of xanthan after previous removal of pyruvylated mannose residues from the ends of the native xanthan side chains by xanthan lyase treatment (XLT-xanthan). Compared with xanthanase from Paenibacillus nanensis, xanthanase CspXan9 had a different module composition at the N-and C-terminal ends. The main putative oligosaccharides released from XLT-xanthan by CspXan9 cleavage were tetrasaccharides and octasaccharides. To explore the functions of the N-and C-terminal regions of the enzyme, truncated variants lacking some of the non-catalytic modules (CspXan9-C, CspXan9-N, CspXan9-C-N) were produced. Enzyme assays with the purified deletion derivatives, which all contained the catalytic glycoside hydrolase family 9 (GH9) module, demonstrated substantially reduced specific activity on XLT-xanthan of CspXan9-C-N compared with full-length CspXan9. The C-terminal module of CspXan9 was found to represent a novel carbohydrate-binding module of family CBM66 with binding affinity for XLT-xanthan, as was shown by native affinity polyacrylamide gel electrophoresis in the presence of various polysaccharides. The only previously known binding function of a CBM66 member is exo-type binding to the non-reducing fructose ends of the -fructan polysaccharides inulin and levan.